High-temperature-resistant metal ceramic-based self-lubricating composite material and preparation method thereof
By using high-entropy alloys such as CoCrNiFeMn and Ti3SiC2, high-temperature cermet-based self-lubricating composite materials, the problems of poor mechanical properties and complex preparation processes of existing materials at high temperatures are solved, and higher mechanical properties and a simplified preparation process are achieved.
Patent Information
- Application Number
- CN202510037376.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-04
Smart Images

Figure CN119753481A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to a high-temperature resistant metal ceramic-based self-lubricating composite material and a preparation method thereof. Background Art
[0002] Metal ceramic-based self-lubricating composite materials have high hardness, high wear resistance, high melting point, high oxidation resistance and high corrosion resistance, and are widely used in mechanical equipment that serve under very harsh working conditions such as high temperature, ultra-low temperature, ultra-high vacuum, strong oxidation and strong radiation. Through reasonable composition and process design, metal ceramic-based self-lubricating composite materials can show advantages that traditional materials cannot match, such as high hardness, excellent wear resistance, high temperature oxidation resistance and good thermal stability.
[0003] Deficiencies of existing technology: Wang Zongshi [Wang Zongshi. Preparation and performance study of new Ti(C,N)-based cermet coated tools with high entropy alloy as binder [D]. Sichuan University, 2021.] Using the five-element high entropy alloy (HEA) CoCrCuFeNi prepared by mechanical alloying as a binder, a Ti(C,N)-HEA cermet composite with high comprehensive performance was successfully prepared, and the effect of CoCrCuFeNi HEA binder on the microstructure, basic mechanical properties and high-temperature friction and wear properties of Ti(C,N)-based cermet materials was studied. The study found that the HEA binder can inhibit the growth of core ring grains and promote the formation of finer white core grains, significantly improving its hardness up to 1726 HV, significantly reducing the friction coefficient, and its wear resistance is 2.5 times that of the Ti(C,N)-Ni cermet composite. However, it has the problem of complex preparation process. Fang Yihang [Fang Yihang. Research on the synergistic strengthening and toughening of Ti(C,N)-based metal ceramics by whiskers and high entropy alloys [D]. Nanchang University, 2020.] Ti(C,N)-based metal ceramic composites synergistically strengthened and toughened by whiskers and high entropy alloys were prepared by hot pressing sintering. 2 Whiskers and Al 0.3 The preparation of CoCrFeNi high entropy alloy (HEA) and the research on the microstructure, mechanical properties and high temperature performance of Ti(C,N) based cermets have laid a solid theoretical and application foundation for the development of Ti(C,N) based cermets with high hardness and good toughness. 2 C-TaC-Ni / Co cermets. When the Ti(C,N) content is 70 wt.% and the Ni / Co content is 10 wt.%, the relative density, hardness, flexural strength and fracture toughness reach 99.1%, 19.39 GPa, 1488 MPa and 7.84 MPa·m respectively. 1 / 2When the Ti(C,N) content is 55 wt.% and the Ni / Co content is 25 wt.%, the relative density, hardness, flexural strength and fracture toughness reach 99.39%, 12.71 GPa, 1674 MPa and 8.99 MPa·m respectively. 1 / 2 . However, it has the problems of complicated preparation process, long time consumption and high purity requirements of raw materials, which is not conducive to industrial production. Wang Yanjun et al. [Wang Yanjun, Liu Zuomin, Yang Liying. High-temperature self-lubricating properties and lubrication mechanism of infiltration-type TiC / FeCrWMoV metal ceramics [J]. Journal of Materials Science and Engineering, 2009, 27(06): 850-854+849.] used the vacuum pressure infiltration composite technology of molten solid lubricant and microporous metal ceramic preform to prepare an infiltration-type interpenetrating network structure TiC / FeCrWMoV metal ceramic composite material. The composite material has good self-lubricating properties in a wide temperature range. However, it has the problems of low hardness and large mass loss. Summary of the invention
[0004] The purpose of the present invention is to provide a high temperature resistant metal ceramic based self-lubricating composite material and a preparation method thereof, so as to solve the problems of poor high temperature mechanical properties, high wear rate and complicated preparation process of the composite material.
[0005] High temperature resistant metal ceramic based self-lubricating composite material, the mass fraction of high entropy alloy CoCrNiFeMn in the high temperature resistant metal ceramic based self-lubricating composite material is 50~70wt.%, and the non-stoichiometric hard phase TiC 0.4 The mass fraction of solid lubricating phase Ti is 10~16.7wt.%. 3 SiC 2 The mass fraction is 20~33.4wt.%.
[0006] The present invention also provides a method for preparing a high temperature resistant metal ceramic-based self-lubricating composite material. In the preparation process, the method for preparing a high temperature resistant metal ceramic-based self-lubricating composite material comprises the following steps: S1 preparation of a non-stoichiometric hard phase; S2 preparation of a high entropy alloy raw material; S3 raw material mixing; S4 powder metallurgy sintering, wherein: S1. Preparation of non-stoichiometric hard phase raw materials: TiC 0.4 The preparation of powders can be found in China: CN108754275B; S2. Preparation of high entropy alloy powder: Using the metal powder of the high entropy alloy component as the raw material, weigh each metal powder according to the established ratio and then use the mechanical alloying method to prepare the high entropy alloy powder, the ball-to-material ratio is 10:1~20:1, the rotation speed is 300~450 r / min, and the ball milling time is 5~40 h; S3, raw material mixing: including two methods: a. CoCrNiFeMn high entropy alloy powder, TiCx powder and Ti 3 SiC 2 The particles are ball-milled to obtain composite powder, with a ball-to-material ratio of 10:1-20:1, a rotation speed of 300-450 r / min, and a ball-milling time of 2-20 h; b. In an argon atmosphere, Co powder, Cr powder, Ni powder, Fe powder, Mn powder, TiCx powder and Ti powder with a predetermined ratio are added. 3 SiC 2 The particles are ball-milled to obtain composite powder, with a ball-to-material ratio of 10:1-20:1, a rotation speed of 300-450 r / min, and a ball-milling time of 2-20 h; S4, powder metallurgy sintering: including any one of the methods (7) spark plasma sintering; (8) vacuum hot pressing sintering, wherein: (7) Spark plasma sintering: pre-pressing the raw material obtained by mixing the raw materials in step S3, the pre-pressing pressure is 10-500 MPa, the pre-pressing is 1-3 min, and then spark plasma sintering is performed, the vacuum degree is 10-40 Pa, the sintering pressure is 10-50 MPa, the sintering temperature is 1000-1600 ° C, the heating rate is 30-100 ° C / min, and the holding time is 3-30 min; then the temperature is reduced and the pressure is released to obtain a high temperature resistant metal ceramic-based self-lubricating composite material; (8) Vacuum hot pressing sintering: pre-pressing the raw materials mixed in step S3, the pre-pressing pressure is 10-500 MPa, the pre-pressing is 1-3 min, and then vacuum hot pressing sintering is performed, the vacuum degree is 10-40 Pa, the sintering pressure is 40-100 MPa, the sintering temperature is 1000-1600 ° C, the heating rate is 10-30 ° C / min, the holding time is 5-30 min, and then the temperature is reduced and the pressure is released to obtain a high temperature resistant metal ceramic-based self-lubricating composite material; Furthermore, in the preparation method S3, the raw material mixing to prepare the high temperature resistant metal ceramic based self-lubricating composite material composite powder needs to be pre-pressed.
[0007] Furthermore, after obtaining the blank in the powder metallurgy sintering method (7) spark plasma sintering and (8) vacuum hot pressing sintering in step S4 of the preparation method, the prepared blank is subjected to surface grinding and deburring treatment to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0008] Compared with the prior art, the present invention has the following beneficial effects: The preparation process of the high temperature resistant metal ceramic based self-lubricating composite material of the present invention, including raw material preparation, material mixing and sintering processes, is applicable to the preparation of all metal ceramic based self-lubricating composite materials.
[0009] The high entropy alloy phase selected in the present invention can be mixed by directly adding metal element powder, and the material can be taken in the air, which can simplify the preparation process to a certain extent and reduce the production cost; The invention improves the mechanical properties of the composite material by utilizing the unique properties of the metal ceramic material itself.
[0010] Solid lubricating phase Ti 3 SiC 2 The addition of TiC can provide good lubrication effect, making it have a stable friction coefficient in the range of 25~500 ℃. 0.4 The addition of can improve the interface bonding between the phases and improve the mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a flow chart of the high temperature resistant high entropy alloy based self-lubricating composite material and its preparation method of the present invention; Figure 2 XRD diagram of the high temperature resistant metal ceramic based self-lubricating composite material obtained in 1; Figure 3 XRD diagram of the high temperature resistant metal ceramic based self-lubricating composite material obtained in implementation 2; Figure 4 XRD diagram of the high temperature resistant metal ceramic based self-lubricating composite material obtained in implementation 3; Figure 5 The surface SEM image of the sintered body of the high temperature resistant metal ceramic-based self-lubricating composite material obtained in implementation 3; Figure 6 for Figure 5 Atomic percentage of each region; Figure 7 This is a cross-sectional SEM image of the sintered body of the high temperature resistant metal ceramic-based self-lubricating composite material obtained in implementation 3; Figure 8 for Figure 7 Atomic percentage of each region; Fig. 9 The SEM image of the friction and wear surface of the high temperature resistant metal ceramic based self-lubricating composite material at room temperature obtained in Implementation 3; Fig.10 for Fig. 9 Atomic percentage of each region; Fig.11 SEM image of the high temperature friction and wear surface of the high temperature resistant metal ceramic-based self-lubricating composite material prepared in Implementation 3; Fig.12 for Fig.11 Atomic percentage of each region; Fig.13 XRD diagram of the high temperature resistant metal ceramic based self-lubricating composite material obtained in 4; Fig.14 This is the XRD pattern of the high temperature resistant metal ceramic based self-lubricating composite material prepared in implementation 5. DETAILED DESCRIPTION
[0012] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0013] Example 1 See also Figure 1 , the present invention provides the following technical solution: a high-temperature resistant metal ceramic-based self-lubricating composite material is composed of 60wt.% of a high-entropy alloy raw material, 13.33wt.% of a non-stoichiometric hard phase and 26.67wt.% of a solid lubricating phase. The present invention also provides a method for preparing a high-temperature resistant metal ceramic-based self-lubricating composite material: five metal element powders, Co, Cr, Ni, Fe and Mn, are weighed separately (the purity is all >99%, the particle size of Co powder and Ni powder is 1~3 μm, the particle size of Cr powder is 5 μm, and the particle size of the other metal powders is <46 μm), the molar amount of each metal element powder is equal, the particle size of Ti powder is <30 μm, the particle size of TiC powder is 1~3 μm, and the particle size of Ti 3 SiC 2 The particle size is 425~850 μm; five metal single substance powders of Co, Cr, Ni, Fe and Mn are loaded into a steel ball ball mill, and steel grinding balls are loaded according to the ball-to-material mass ratio of 10:1, and ball milling is carried out in an argon atmosphere (the rotation speed is 350 r / min, the total ball milling time is 30 h, and the machine is stopped for 20 min every 1 h for heat dissipation), and the raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed every 10 h, and then 0.2 ml / 10 g of anhydrous ethanol dispersant of the mixed powder is added to continue ball milling) to obtain CoCrNiFeMn high entropy alloy powder; the preparation of TiCx powder can be found in China: CN108754275B; then CoCrNiFeMn high entropy alloy powder, TiCx powder and Ti 3 SiC 2The powders were loaded into a steel ball milling jar in proportion, and steel grinding balls were loaded according to the ball-to-material mass ratio of 10:1. The materials were milled and mixed in an argon atmosphere (the speed was 300 r / min, the ball milling time was 10 h, and the machine was stopped for 30 min for heat dissipation every 1 h), and the materials were taken out in a glove box; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively, and the mass ratios of large, medium and small balls were 6:3:1; the mixed materials were loaded into a graphite mold for pre-pressing, and the pre-pressing pressure was 30 MPa for 1 min. Then, spark plasma sintering was performed, the vacuum degree was 40 Pa, and the pressure was increased to 50 MPa; then, it was heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 10 min; then, the temperature was increased from 600 ℃ to 1100 ℃ at a heating rate of 70 ℃ / min, and kept at this temperature for 10 min. After cooling with the furnace, a blank was obtained. The surface of the blank was polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0014] The obtained high temperature resistant metal ceramic based self-lubricating composite material samples were polished and then tested for performance. The technical parameters of the obtained sintered body are shown in Table 1, and the XRD pattern of the composite material is shown in Figure 2 .
[0015] Table 1 Performance parameters and specific values of the high temperature resistant metal ceramic based self-lubricating composite material in Example 1 Example 2
[0016] See also Figure 1 , the present invention provides the following technical solution: a high-temperature resistant metal ceramic-based self-lubricating composite material is composed of 70wt.% of a high-entropy alloy raw material, 10wt.% of a non-stoichiometric hard phase and 20wt.% of a solid lubricating phase. The present invention also provides a method for preparing a high-temperature resistant metal ceramic-based self-lubricating composite material: five metal element powders, Co, Cr, Ni, Fe and Mn, are weighed separately (the purity is all >99%, the particle size of Co powder and Ni powder is 1~3 μm, the particle size of Cr powder is 5 μm, and the particle size of the other metal powders is <46μm), the molar amount of each metal element powder is equal, the particle size of Ti powder is <30 μm, the particle size of TiC powder is 1~3 μm, and the particle size of Ti 3 SiC 2The particle size is 425~850 μm; five metal single substance powders of Co, Cr, Ni, Fe and Mn are loaded into a steel ball ball mill, and steel grinding balls are loaded according to the ball-to-material mass ratio of 10:1, and ball milling is carried out in an argon atmosphere (the speed is 350 r / min, the total ball milling time is 30h, and the machine is stopped for 20 min every 1 h for heat dissipation), and the raw materials adhering to the grinding balls and the inner wall of the jar are scraped off and mixed every 10 h, and then 0.2 ml / 10 g of anhydrous ethanol dispersant of the mixed powder is added to continue ball milling) to obtain CoCrNiFeMn high entropy alloy powder; the preparation of TiCx powder can be found in China: CN108754275B; then CoCrNiFeMn high entropy alloy powder, TiCx powder and Ti 3 SiC 2 The powders were loaded into a steel ball milling jar in proportion, and steel grinding balls were loaded according to the ball-to-material mass ratio of 10:1. The materials were milled and mixed in an argon atmosphere (the speed was 300 r / min, the ball milling time was 10 h, and the machine was stopped for 30 min for heat dissipation every 1 h), and the materials were taken out in a glove box; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively, and the mass ratios of large, medium and small balls were 6:3:1; the mixed materials were loaded into a graphite mold for pre-pressing, and the pre-pressing pressure was 30 MPa for 1 min. Then, spark plasma sintering was performed, the vacuum degree was 40 Pa, and the pressure was increased to 50 MPa; then, it was heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 10 min; then, the temperature was increased from 600 ℃ to 1100 ℃ at a heating rate of 70 ℃ / min, and kept at this temperature for 10 min. After cooling with the furnace, a blank was obtained. The surface of the blank was polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0017] The obtained high temperature resistant metal ceramic based self-lubricating composite material samples were polished and then tested for performance. The technical parameters of the obtained sintered body are shown in Table 2, and the XRD pattern of the composite material is shown in Figure 3 .
[0018] Table 2 High temperature resistant metal ceramic based self-lubricating composite materials and specific values in Example 2 Example 3
[0019] See also Figure 1, the present invention provides the following technical solution: a high-temperature resistant metal ceramic-based self-lubricating composite material is composed of 60wt.% of a high-entropy alloy raw material, 13.33wt.% of a non-stoichiometric hard phase and 26.67wt.% of a solid lubricating phase. The present invention also provides a method for preparing a high-temperature resistant high-entropy alloy-based self-lubricating composite material: five metal single substance powders of Co, Cr, Ni, Fe and Mn are weighed separately (the purity is all >99%, the particle size of Co powder and Ni powder is 1~3 μm, the particle size of Cr powder is 5 μm, and the particle size of the other metal powders is <46 μm), the molar amount of each metal single substance powder is equal, the particle size of Ti powder is <30 μm, the particle size of TiC powder is 1~3 μm, and the particle size of Ti 3 SiC 2 The particle size is 425~850 μm; five metal single substance powders of Co, Cr, Ni, Fe and Mn are loaded into a steel ball ball mill, and steel grinding balls are loaded according to the ball-to-material mass ratio of 10:1, and ball milling is carried out in an argon atmosphere (the rotation speed is 350 r / min, the total ball milling time is 30 h, and the machine is stopped for 20 min every 1 h for heat dissipation), and the raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed every 10 h, and then 0.2 ml / 10 g of anhydrous ethanol dispersant of the mixed powder is added to continue ball milling) to obtain CoCrNiFeMn high entropy alloy powder; the preparation of TiCx powder can be found in China: CN108754275B; then CoCrNiFeMn high entropy alloy powder, TiCx powder and Ti 3 SiC 2 The powders were loaded into a steel ball milling jar in proportion, and steel grinding balls were loaded according to the ball-to-material mass ratio of 10:1. The materials were milled and mixed in an argon atmosphere (the speed was 300 r / min, the ball milling time was 2 h, and the machine was stopped for 30 min for heat dissipation after every 1 h of rotation). The materials were taken out in the air. The diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively, and the mass ratios of large, medium and small balls were 6:3:1. The mixed materials were loaded into a graphite mold for pre-pressing, and the pre-pressing pressure was 30 MPa for 1 min. Then, spark plasma sintering was performed, the vacuum degree was 40Pa, and the pressure was increased to 50 MPa. Then, it was heated from room temperature to 600 °C in 5 min, and kept at 600 °C for 10 min. Then, the temperature was increased from 600 °C to 1200 °C at a heating rate of 70 °C / min, and kept at this temperature for 10 min. The blank was cooled with the furnace to obtain the blank. The surface of the blank was polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0020] The obtained high temperature resistant metal ceramic based self-lubricating composite material samples were polished and then the organization and performance were tested. The technical parameters of the obtained sintered body are shown in Table 3, and the XRD pattern of the composite material is shown in Figure 4 . Figure 5 The surface SEM image of the sintered body of the high temperature resistant metal ceramic-based self-lubricating composite material obtained in implementation 3; Figure 6 for Figure 5 Atomic percentage of each region; Figure 7 This is a cross-sectional SEM image of the sintered body of the high temperature resistant metal ceramic-based self-lubricating composite material obtained in implementation 3; Figure 8 for Figure 7 Atomic percentage of each region; Fig. 9 The SEM image of the friction and wear surface of the high temperature resistant metal ceramic based self-lubricating composite material at room temperature obtained in Implementation 3; Fig.10 for Fig. 9 Atomic percentage of each region; Fig.11 SEM image of the high temperature friction and wear surface of the high temperature resistant metal ceramic-based self-lubricating composite material prepared in Implementation 3; Fig.12 for Fig.11 Atomic percentage of each region.
[0021] Table 3 Performance parameters and specific values of the high temperature resistant metal ceramic based self-lubricating composite material in Example 3 Example 4
[0022] See also Figure 1 , the present invention provides the following technical solution: a high-temperature resistant metal ceramic-based self-lubricating composite material is composed of 12.61wt.% Co powder, 11.12wt.% Cr powder, 12.56wt.% Ni powder, 11.96wt.% Fe powder, 11.75wt.% Mn powder, 13.33wt.% non-stoichiometric hard phase and 26.67wt.% solid lubricating phase. The present invention also provides a method for preparing a high-temperature resistant high-entropy alloy-based self-lubricating composite material: five metal single substance powders of Co, Cr, Ni, Fe and Mn are weighed separately (the purity is all >99%, the particle size of Co powder and Ni powder is 1~3 μm, the particle size of Cr powder is 5 μm, and the particle size of the other metal powders is <46 μm), the molar amount of each metal single substance powder is equal, the particle size of Ti powder is <30 μm, the particle size of TiC powder is 1~3 μm, and the particle size of TiC powder is <46 μm. 3 SiC 2 The particle size is 425~850 μm; the preparation of TiCx powder can be found in China: CN108754275B; then five metal powders of Co, Cr, Ni, Fe, Mn, TiCx powder and Ti 3 SiC 2The powders were loaded into a steel ball milling jar in proportion, and steel grinding balls were loaded according to the ball-to-material mass ratio of 10:1. The materials were milled and mixed in an argon atmosphere (the speed was 300 r / min, the ball milling time was 10 h, and the machine was stopped for 30 min for heat dissipation after every 1 h of rotation). The materials were taken out in the air. The diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively, and the mass ratios of large, medium and small balls were 6:3:1. The mixed materials were loaded into a graphite mold for pre-pressing, and the pre-pressing pressure was 30 MPa for 1 min. Then, spark plasma sintering was performed, the vacuum degree was 40 Pa, and the pressure was increased to 50 MPa. Then, it was heated from room temperature to 600 °C in 5 min, and kept at 600 °C for 10 min. Then, the temperature was increased from 600 °C to 1200 °C at a heating rate of 70 °C / min, and kept at this temperature for 10 min. The blank was cooled with the furnace to obtain the blank. The surface of the blank was polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0023] The obtained high temperature resistant metal ceramic based self-lubricating composite material samples were polished and then the organization and performance were tested. The technical parameters of the obtained sintered body are shown in Table 4, and the XRD pattern of the composite material is shown in Fig.13 .
[0024] Table 4 Performance parameters and specific values of the high temperature resistant metal ceramic based self-lubricating composite material in Example 4 Example 5
[0025] See also Figure 1 , the present invention provides the following technical solution: a high-temperature resistant metal ceramic-based self-lubricating composite material is composed of 50wt.% of a high-entropy alloy raw material, 16.67wt.% of a non-stoichiometric hard phase and 33.33wt.% of a solid lubricating phase. The present invention also provides a method for preparing a high-temperature resistant metal ceramic-based self-lubricating composite material: five metal element powders, Co, Cr, Ni, Fe and Mn, are weighed separately (the purity is all >99%, the particle size of Co powder and Ni powder is 1~3 μm, the particle size of Cr powder is 5 μm, and the particle size of the other metal powders is <46 μm), the molar amount of each metal element powder is equal, the particle size of Ti powder is <30 μm, the particle size of TiC powder is 1~3 μm, and the particle size of Ti 3 SiC 2The particle size is 425~850 μm; five metal single substance powders of Co, Cr, Ni, Fe and Mn are loaded into a steel ball ball mill, and steel grinding balls are loaded according to the ball-to-material mass ratio of 10:1, and ball milling is carried out in an argon atmosphere (the rotation speed is 350 r / min, the total ball milling time is 30 h, and the machine is stopped for 20 min every 1 h for heat dissipation), and the raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed every 10 h, and then 0.2 ml / 10 g of anhydrous ethanol dispersant of the mixed powder is added to continue ball milling) to obtain CoCrNiFeMn high entropy alloy powder; the preparation of TiCx powder can be found in China: CN108754275B; then CoCrNiFeMn high entropy alloy powder, TiCx powder and Ti 3 SiC 2 The powders were loaded into a steel ball milling jar in proportion, and steel grinding balls were loaded according to the ball-to-material mass ratio of 10:1. The materials were milled and mixed in an argon atmosphere (the speed was 300 r / min, the ball milling time was 10 h, and the machine was stopped for 30 min for heat dissipation every 1 h), and the materials were taken out in a glove box; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively, and the mass ratios of large, medium and small balls were 6:3:1; the mixed materials were loaded into a graphite mold for pre-pressing, and the pre-pressing pressure was 30 MPa for 1 min. Then, spark plasma sintering was performed, the vacuum degree was 40 Pa, and the pressure was increased to 50 MPa; then, it was heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 10 min; then, the temperature was increased from 600 ℃ to 1100 ℃ at a heating rate of 70 ℃ / min, and kept at this temperature for 10 min. After cooling with the furnace, a blank was obtained. The surface of the blank was polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0026] The obtained high temperature resistant metal ceramic based self-lubricating composite material samples were polished and then tested for performance. The technical parameters of the obtained sintered body are shown in Table 7, and the XRD pattern of the composite material is shown in Fig.14 .
[0027] Table 7 High temperature resistant metal ceramic based self-lubricating composite materials and specific values in Example 5
[0028] In summary, the present invention has the following beneficial effects: 1. The preparation process of the high temperature resistant metal ceramic-based self-lubricating composite material of the present invention, including raw material preparation, mixing and sintering processes, is applicable to the preparation of all metal ceramic-based self-lubricating composite materials.
[0029] 2. The high entropy alloy phase selected in the present invention can be mixed by directly adding metal element powder, and the material can be taken in the air, which can simplify the preparation process to a certain extent and reduce the production cost; 3. The present invention improves the mechanical properties of the composite material by utilizing the unique properties of the metal ceramic material itself.
[0030] 4. The addition of solid lubricating phase Ti3SiC2 can provide good lubrication effect, making it have a stable friction coefficient in the range of 25~500 ℃. The addition of TiC0.4 can improve the interface bonding between the phases and improve the mechanical properties of the composite material.
[0031] It should be noted that the high entropy alloy described herein includes all equimolar or non-equimolar high entropy alloys, or metal element powders constituting the components of the high entropy alloy (e.g., Mg, Al, Si, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Ag, Hf, Ta, W, Pt, Au, Ga, Li, Sn, Sr, Yb, etc.). The non-stoichiometric hard phase described herein includes non-stoichiometric nitrides, carbides or borides of transition metals (Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W). The solid lubricant described herein is Ti 3 SiC 2 、Ti 3 AlC 2 、Ti 2 AlC、Ti 2 AlN、Ta 2 MAX metal ceramic materials such as AlC. In this article, relational terms such as first and second, etc. are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also includes elements that are inherent to such process, method, article or device. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high temperature resistant metal ceramic based self-lubricating composite material, characterized in that: The mass fraction of high-entropy alloy CoCrNiFeMn of high-temperature resistant metal ceramic-based self-lubricating composite material is 50~70wt.%, and the non-stoichiometric hard phase TiC 0.4 The mass fraction of the solid lubricating phase Ti3SiC2 is 10~16.7wt.%, and the mass fraction of the solid lubricating phase Ti3SiC2 is 20~33.4wt.%.
2. A method for preparing a high temperature resistant metal ceramic based self-lubricating composite material as claimed in claim 1, characterized in that: This preparation process comprises the following steps: S1 non-stoichiometric hard phase raw material preparation; S2 high entropy alloy preparation; S3 raw material mixing; S4 powder metallurgy sintering, including: S1. Preparation of non-stoichiometric hard phase raw materials: see China: CN108754275B; S2. Preparation of high entropy alloys: including any one of the following methods: (1) mechanical alloying; (2) metal element powder; (3) vacuum melting and gas atomization, wherein: Mechanical alloying method: Using the metal powder of the high entropy alloy component as the raw material, weigh each metal powder according to the established ratio and then use the mechanical alloying method to prepare the high entropy alloy powder. The ball-to-material ratio is 10:1-20:1, the rotation speed is 300-450 r / min, and the ball milling time is 5-40 h; Metal powder: The powder of the high entropy alloy component is used as a binder and mixed by ball milling. The ball-to-material ratio is 10:1-20:1, the rotation speed is 300-450 r / min, and the ball milling time is 2-40 h. Vacuum melting gas atomization method: Using the single substance powder of high entropy alloy components as raw materials, high entropy alloy powder is prepared by vacuum melting gas atomization method; S3, raw material mixing: including any one of the methods (4) ball milling mixing method; (5) mechanical alloying method and (6) vacuum melting gas atomization method, wherein: Ball milling mixing method: The high temperature resistant metal ceramic-based self-lubricating composite powder is prepared by ball milling mixing method, the ball-to-material ratio is 10:1-20:1, the rotation speed is 300-450 r / min, and the ball milling time is 2-20 h; Mechanical alloying method: The high temperature resistant metal ceramic based self-lubricating composite powder is obtained by mechanical alloying method, the ball to material ratio is 10:1-20:1, the rotation speed is 300-450 r / min, and the ball milling time is 2-20 h; Vacuum melting gas atomization method: The high entropy alloy precursor powder is prepared by vacuum melting gas atomization method. During the atomization powder spraying process, the above-mentioned hard phase raw materials are added according to a predetermined ratio, and finally a high-temperature resistant metal ceramic-based self-lubricating composite powder is obtained by gas atomization method; S4, powder metallurgy sintering: including any one of the methods (7) spark plasma sintering and (8) vacuum hot pressing sintering, wherein: Spark plasma sintering: pre-pressing the composite powder obtained by mixing the raw materials in step S3, the pre-pressing pressure is 10-500MPa, the pre-pressing is 1-3 min, and then spark plasma sintering is performed, the vacuum degree is 10-40 Pa, the sintering pressure is 10-50 MPa, the sintering temperature is 1000-1600 ℃, the heating rate is 30-100 ℃ / min, and the holding time is 3-30 min; then the temperature is reduced and the pressure is released to obtain a high temperature resistant metal ceramic-based self-lubricating composite powder; Vacuum hot pressing sintering: pre-press the composite powder obtained by mixing the raw materials in step S3, the pre-pressing pressure is 10-500MPa, the pre-pressing is 1-3 min, and then vacuum hot pressing sintering is performed, the vacuum degree is 10-40 Pa, the sintering pressure is 40-100 MPa, the sintering temperature is 1000-1600 ℃, the heating rate is 10-30 ℃ / min, the insulation time is 5-30 min, and then the temperature is reduced and the pressure is released to obtain a high temperature resistant metal ceramic-based self-lubricating composite powder.
3. The high temperature resistant metal ceramic based self-lubricating composite material according to claim 1, wherein the particle size of the high entropy alloy phase is 10 nm-50 μm, and the non-stoichiometric hard phase TiC 0.4 The particle size is 20 nm-50 μm, and the particle size of the solid lubricant phase Ti3SiC2 is 90 μm-900 μm.
4. The method for preparing a high temperature resistant metal ceramic-based self-lubricating composite material according to claim 2, characterized in that: In the preparation method S3, the raw material mixing process for preparing the high temperature resistant metal ceramic based self-lubricating composite material composite powder needs to be pre-pressed.
5. The method for preparing a high temperature resistant high entropy alloy-based self-lubricating composite material according to claim 2, characterized in that: In the preparation method, after obtaining the blank by the powder metallurgy sintering method (7) spark plasma sintering and (8) vacuum hot pressing sintering in step S4, the prepared blank is subjected to surface grinding and deburring treatment to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
Citation Information
Patent Citations
A TiAl-based high-temperature self-lubricating composite material and its preparation method
CN108754275B
Cited By
High-strength wide-temperature-range wide-speed-range self-lubricating metal composite material and preparation method thereof
CN121272261A